Job Competencies of the Psychologist: Systematic Review - Berrío García, Nathaly; Redondo Mendoza, Ciro Ernesto; Escobar Vargas, Carlos José (Pensando Psicología, 2025)
The objective of this systematic review is to compile research reports that show the importance of the labor competencies of psychologists. A search was made of articles in English and Spanish, published between 2010 and 2024, in the databases EBSCO, Dialnet Plus, and ProQuest (Psychology). We included twenty-one studies in the systematic review, of which thirteen met the quality conditions to be assessed in depth. We used the “Framework for Assessing Qualitative Evaluations” of the National Center for Social Research, previously validated by two experts, to evaluate the methodological quality of the qualitative research compiled. The results indicate that the topics on competencies in the different studies include the emergence of the competency model, as well as the classification, description, definition, and evaluation of the different competencies in the training of the psychologist.
Keywords: occupational competences; professional competences; psychologists; systematic review